(untitled) (Iranian Journal of Kidney Diseases, 2024)
Introduction. We recently discovered that microvesicles (MVs) derived from mesenchymal stem cells (MSCs) overexpressing miRNA-34a can alleviate experimental kidney injury in mice. In this study, we further explored the effects of miR34a-MV on renal fibrosis in the unilateral ureteral obstruction (UUO) models. Methods. Bone marrow MSCs were modified by lentiviruses overexpressing miR-34a, and MVs were collected from the supernatants of MSCs. C57BL6/J mice were divided into control, unilateral ureteral obstruction (UUO), UUO + MV, UUO + miR-34aMV and UUO + miR-34a-inhibitor-MV groups. MVs were injected to mice after surgery. The mice were then euthanized on day 7 and 14 of modeling, and renal tissues were collected for further analyses by Hematoxylin and eosin, Masson’s trichrome, and Immunohistochemical (IHC) staining. Results. The UUO + MV group exhibited a significantly reduced degree of renal interstitial fibrosis with inflammatory cell infiltration, tubular epithelial cell atrophy, and vacuole degeneration compared with the UUO group. Surprisingly, overexpressing miR-34a enhanced these effects of MSC-MV on the UUO mice. Conclusion. Our study demonstrates that miR34a further enhances the effects of MSC-MV on renal fibrosis in mice through the regulation of epithelial-to-mesenchymal transition (EMT) and Notch pathway. miR-34a may be a candidate molecular therapeutic target for the treatment of renal fibrosis. DOI: 10.52547/ijkd.7673